Effects of brachiaria grasses on soil microbial biomass carbon, nitrogen and phosphorus in soils of the semi-arid tropics of Kenya - Gichangi, Elias M.; Njarui, Donald M.G.; Gatheru, M.J.; Ndung'u-Magiroi, Keziah Wairimu; Ghimire, Sita R. (2016)
A study was conducted to investigate the changes in microbial biomass carbon (C), nitrogen (N) and phosphorus (P) following cultivation of Brachiaria grasses in semi-arid region of Kenya. The Brachiaria grass cultivars included Brachiaria decumbens cv. Basilisk, B. brizantha cvs Marandu, MG4, Piatã and Xaraes, B. humidicola cv. Llanero and B. hybrid cv. Mulato II which were compared with two locally cultivated forage grasses (Chloris gayana cv. KAT R3 and Pennisetum purpureum cv. Kakamega 1) and a bare plot (negative check). The grass treatments were evaluated with fertilizers application (40 kg P applied at sowing and 50 kg N ha-1 in each wet season) and with no fertilizer applications. Microbial biomass C, N and P were determined on field moist rhizosphere soil (18-23% by weight) from a depth of 10 cm. Microbial biomass was influenced (p < 0.01) by grass cultivars and N and P fertilizers. Generally, microbial biomass N was higher in plots with grasses than in the bare plots. A significant enrichment of organic matter was noted in the microbial biomass when Brachiaria grasses are grown with N and P fertilizers. Among Brachiaria cultivars, the highest microbial biomass C was recorded in plots with cv. Mulato II and the lowest from the plots with cv. MG4. Brachiaria grasses with fertilizers application accumulated the highest microbial C and N compared to grasses without fertilizers, but no interaction was observed between fertilizer and grass cultivars. The cv. Marandu had the highest microbial biomass N (21.2 mg N kg-1) in fertilizer treatments whereas cv. Mulato II hybrid had the highest microbial N (14.6 mg N kg-1) in no fertilizer treatments.